New Markers of Early Cardiovascular Risk in Multiple Sclerosis Patients: Oxidized-LDL Correlates with Clinical Staging. Issue 5 (22nd May 2013) - Palavra, Filipe; Marado, Daniela; Mascarenhas-Melo, Filipa; Sereno, José; Teixeira-Lemos, Edite; Nunes, Carla Cecília; Gonçalves, Grilo; Teixeira, Frederico; Reis, Flávio
Abstract : OBJECTIVES: This study aimed to characterize a population of multiple sclerosis (MS) patients in terms of traditional and new cardiovascular risk factors and assess their putative correlation with clinical disease activity (evaluated by the Expanded Disability Status Scale [EDSS]). METHODS: Thirty relapsing MS patients and 66 subjects, matched by age and sex, were enrolled in this cross-sectional study. For each subject, anthropometric data were collected and classical biochemical (including lipid profile, glucose and C reactive protein [CRP] levels) and novel markers (paraoxonase 1 [PON1] enzyme activity and contents of high-density lipoprotein [HDL] cholesterol, oxidized low-density lipoprotein [Ox-LDL], tumor necrosis factor [TNF]-alfa, vascular endothelial growth factor [VEGF] and adiponectin) were studied. RESULTS: In patients group, 23 women and 7 men were included, aged 35.00 (28.25–40.25) years and scoring a median of 2.00 (1.50–3.13) in EDSS. Comparing with controls, the most relevant differences encountered were: increased serum triglycerides ( P < 0.001), Ox-LDL ( P < 0.001) as well as Ox-LDL/LDL ratio and reduced small HDL ( P = 0.040), accompanied by a trend to increased VEGF concentration. LDL content, especially Ox-LDL, showed positive and significant correlation with EDSS ( r = 0.458; P = 0.011) and VEGF ( r = 0.453; P = 0.014). CONCLUSIONS: MS patients presented a profile of early CV risk, being Ox-LDL contents a putative good marker and having correlation with the clinical activity of the disease.